PENGARUH PENDEKATAN DEDUKTIF TERHADAP HASIL BELAJAR MAHASISWA PRODI PENDIDIKAN EKONOMI - Emilia Dewiwati Pelipa; Anna Marganingsih (STKIP Persada Khatulistiwa Sintang, 2022)
This study aims to determine the effect of the deductive approach on student learning outcomes in financial management courses on the basic concept material for the capital budgeting program in Economics education studies at STKIP Persada Khatulistiwa sintang. The financial management course is one of the compulsory courses and the material for the basic concepts of capital budgeting is the core material of the financial management course. This study uses experimental research methods with a quasy experimental research design with nonequivalent control group design. The results showed that the pretest in the experimental group and the control group showed that tcount -1.301 was smaller than ttable 2.048. The posttest in the experimental group and the control group showed that the tcount was 2.254 greater than the ttable 2.048. The results of the pretest and posttest in the experimental group showed a tcount of 8.035 greater than a ttable of 2.048). Based on the research results, it can be interpreted that there is an influence of the deductive approach on student learning outcomes in financial management courses on the basic concepts of capital budgeting